Beyond Normal Limits: Analysis Standard Social Culture in Children with Special Needs - Daniel Ebenezer Silaban; M. Syafii (Universitas Muhammadiyah Mataram, 2024)
This research aims to investigate the perceptions and stereotypes within cultural social simulations concerning children with special needs in North Sumatra, as well as their impact on their identity and participation. This research employs to Qualitative investigate inclusive education in North Sumatra. Interviews are conducted with a diverse group, including parents of children with special needs, Three teachers from inclusive schools (SMA Cahaya, Methodis and SMKN 10 Medan, and one employe representatives from the North Sumatra Provincial Education Office. These conversations aim to gather personal insights and experiences regarding the challenges and successes of inclusive education. Alongside, an extensive analysis of documents, such as policies, guidelines, and regulations governing inclusive education, is undertaken. This approach enables a comprehensive understanding of the current state of inclusive education, identifying both the practical and systemic barriers to its effective implementation. Through this methodology, the research seeks to offer a nuanced perspective on how inclusive education is perceived and enacted in North Sumatra, highlighting areas for improvement and potential strategies for advancement. The findings indicate that negative perceptions and stereotypes still influence children with special needs in cultural social simulations, affecting their identity and limiting their participation. Despite efforts towards inclusive education in North Sumatra, regulations and implementation face challenges. Therefore, further efforts are needed to raise public awareness, support more effective inclusive education, change perceptions and stereotypes, and ensure a positive identity and full participation for children with special needs